PENERAPAN MATEMATIKA PADA ILMU EKONOMI : BILANGAN RIIL DAN PERTIDAKSAMAAN - Dini, Dini Nur Aulia Marsya; Khoirul, M.; Lestari, Nadia; Fara Amelia, Nidia; Saputra L, Novanda Dewa; Anggraeni, Prita Dwi (JIDE : Journal Of International Development Economics, 2024)
This article discusses the application of mathematics to economics: real numbers and inequalities. Real numbers include various types of numbers used to describe size, length, time, and various other phenomena in everyday life. The purpose of this research is to explore the importance of understanding the real number system and inequalities. The method used in writing this article is the literature review method. This concept includes rational, irrational, and transcendental numbers that can be found in decimal or fractional form. On the other hand, inequality is a relation that describes the comparison between two unequal mathematical expressions, which plays an important role in the analysis of mathematical problems. This article also reviews various applications, contextual problem solving, and technology-based approaches. An understanding of real numbers and inequalities is essential, not only in mathematics, but also in solving economic problems, such as resource planning and personal finance management.